Bank Credit Card and the Selection Criteria: An Exploratory Study - Subramaniam, Ravichandran (2010)
This paper investigates the selection criteria of bank credit cards that contribute towards credit card selection among Malaysian credit card holders. There is a total of 17 providers’ of bank credit cards both from local and foreign banks. The selection of bank credit cards is empirically examined using five series of selection criteria and demographic factors. It is evident that the main crystallised factor in bank selection is the convenience and assurance to cardholder’s factor which is also consistent with prior results. The results found no significant difference on the demographic groups although respondents show concern on the availability of more ATMs and internet to provide more flexible and quality services. The results also show significant difference on the perception towards cash advance, credit limit, annual fee and annual payment rate among different ages and annual income groups. Further, it is evident that the perception towards special discounts, credit card road show, reward’s program and gender reputation differ among marital status, age and annual income of the respondents.